Unanswered questions regarding the pathogenesis of late onset posterior capsular opacification - Rakib-Uz-Zaman, S. M.; Werner, Liliana; Duncan, Melinda K. (Frontiers in Ophthalmology, 2025)
Following extracapsular cataract extraction, residual lens epithelial cells (LECs) are induced to express pro-inflammatory genes within hours of surgery, then begin to proliferate while migrating to populate denuded areas of the lens capsule. If these cells reach the optical axis, they scatter light, resulting in visual disturbances that are clinically defined as Posterior capsular opacification (PCO). Historically, PCO occurred at high rates within weeks or months of surgery, but over the past 10–20 years, this “acute onset” PCO has become relatively rare following cataract surgery in adults, due to improved surgical techniques and the ability of square edge intraocular lens (IOL) implants to block residual LECs from reaching the visual axis. Despite this, PCO rates are still substantial by 5–10 years following cataract surgery, apparently due to the ability of these entrapped cells to escape their confinement at the capsular bag periphery. This review explores the mechanisms by which cataract surgery elicits acute phenotypic changes to LECs and explores how these changes may set the stage for late-onset PCO.